2014
DOI: 10.1016/j.cub.2014.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Dynamics in the Yeast Proteome

Abstract: The activation of transcription factors in response to environmental conditions is fundamental to cellular regulation. Recent work has revealed that some transcription factors are activated in stochastic pulses of nuclear localization, rather than at a constant level, even in a constant environment. In such cases, signals control the mean activity of the transcription factor by modulating the frequency, duration, or amplitude of these pulses. Although specific pulsatile transcription factors have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 37 publications
2
74
2
Order By: Relevance
“…As methods for quantifying intracellular signaling have improved, several signaling pathways have been found to transmit information using signals that pulse in time (Dalal et al, 2014; Levine et al, 2013). Pulsatile signaling has been found to serve diverse purposes in a biological context, including enforcing proportionality in gene expression (Cai et al, 2008), implementing timer processes (Levine et al, 2012), generating different gene expression or phosphorylation patterns (Ashall et al, 2009; Batchelor et al, 2009; Hansen and O’Shea, 2014; Hao and O’Shea, 2012; Nelson et al, 2004; Purvis et al, 2012; Tay et al, 2010; Toettcher et al, 2013), and improving signaling fidelity (Selimkhanov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As methods for quantifying intracellular signaling have improved, several signaling pathways have been found to transmit information using signals that pulse in time (Dalal et al, 2014; Levine et al, 2013). Pulsatile signaling has been found to serve diverse purposes in a biological context, including enforcing proportionality in gene expression (Cai et al, 2008), implementing timer processes (Levine et al, 2012), generating different gene expression or phosphorylation patterns (Ashall et al, 2009; Batchelor et al, 2009; Hansen and O’Shea, 2014; Hao and O’Shea, 2012; Nelson et al, 2004; Purvis et al, 2012; Tay et al, 2010; Toettcher et al, 2013), and improving signaling fidelity (Selimkhanov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors (TFs) are key components of the signaling cascades orchestrating a cell’s response to stress 8 . Curiously, many TFs exhibit dynamic behaviors in response to stress 9,10 . A recent genome-wide screen identified ~8% of the yeast TFs stochastically shuttle in and out of the nucleus under various conditions 9 .…”
Section: Strategies For the Epigenetic Inheritance Of Stress Responsementioning
confidence: 99%
“…Curiously, many TFs exhibit dynamic behaviors in response to stress 9,10 . A recent genome-wide screen identified ~8% of the yeast TFs stochastically shuttle in and out of the nucleus under various conditions 9 . Single-cell studies in recent years have revealed that transcription factors can transmit quantitative information corresponding to distinct environmental conditions 11,12 .…”
Section: Strategies For the Epigenetic Inheritance Of Stress Responsementioning
confidence: 99%
“…This coordination of target gene expression would be difficult to achieve in an amplitude-modulated system where an increase in calcium leads to a proportional increase in nuclear Crz1 concentration, generating different ratios of target gene expression for each concentration of calcium (Figure 2B). A subsequent fluorescence microscopy-based screen by Dalal and colleagues showed that at least twelve different yeast transcription factors undergo similarly noisy short duration, frequency-modulated bursts of nuclear translocation [51]. These results suggest that such noisy transcription factor dynamics may be evolutionarily beneficial for a wide range of cellular responses.…”
Section: Potential Functional Benefits Of Noise In Coordinating Gene mentioning
confidence: 99%